Comparative Study of Biochar and Hydrochar Derived from Agricultural Waste: Characterization and Chemical Properties - Palapa, Neza Rahayu; Hanifah, Yulizah; Amri; Putri, Bunga Indah (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Carbonaceous substances, including hydrochar and biochar, have been produced from agricultural residue via hydrothermal and pyrolysis processes. The surface morphology of the materials was assessed using FTIR, XRD, BET, and SEM techniques. The identification of diffraction peaks at approximately 22° by XRD analysis suggested the existence of carbonaceous material. This is confirmed by FTIR analysis, which identifies cellulose vibration at 2931 cm?1. The results of the SEM analysis revealed that BC-Rice husk and HYC-Rice husk are heterogeneous in shape and surface area; conversely, HYC-Rambutan and Duku have a uniform, ball-like shape and aggregate. This is further corroborated by surface area data, which indicates that the material composed of rice husk has a larger surface area than the material composed of fruit peel.